Model Pembelajaran Multisensori sebagai Upaya Meningkatkan Kemandirian Toilet Training bagi Anak MDVI (Multiple Disability With Visual Impairtment) - Chindy Innayah; Sayidatul Maslahah (Piramida Akademi, 2026)
This study aims to determine the effect of the multisensory learning model on improving toilet training independence in children with Multiple Disability with Visual Impairment (MDVI). The research applied a quantitative approach with a quasi-experimental method and a one-group pretest-posttest design. The subjects consisted of two third-grade MDVI children at SKH Bina Citra Anak, Serang, Banten. The instrument used was an observation sheet including cognitive, affective, and psychomotor indicators to assess the children's level of independence in toilet training activities. The intervention involved applying the multisensory learning model in five sessions over three weeks. This model incorporated various sensory stimulations such as tactile, auditory, kinesthetic, and concrete visual aids tailored to the characteristics of MDVI children. Pre-test results indicated that the children's toilet training independence was still low (R = 50%, WD = 40%). After the intervention, post-test results improved to 75% for subject R and 60% for subject WD. Data analysis using the Wilcoxon Signed Rank Test showed T count = 0 and T table = 0 at a significance level of 0.05, indicating that H₀ is rejected and Hₐ is accepted. This proves that the multisensory learning model has a significant effect on enhancing toilet training independence in children with MDVI. Multisensory-based instruction effectively supports children's understanding and skills in carrying out daily living activities independently.